MAKING WEBSITE AT PT. EMAX FORTUNE INTERNATIONAL USING DREAMWEAVER MX 2004 - Muzayyanah Muzayyanah (Jurnal Sistem Informasi, 2007)
In this scientific writing, the author makes the website of PT. Emax Fortune International using Macromedia Dreamweaver MX 2004. With the expansion of global trade, is not enough for a company that only relies on ads and flyers to promote the business being run. Therefore indirectly stimulate the entrepreneurs to run the business as possible. So with the making of this website, macintosh allow users to view the latest information from Apple products.